Preparation and characterization of zeolite polymer composite proton exchange membrane - Rosdi, A.N.; Yee, L.K.; Purushothaman, M.; Ibrahim, S.; Pichiah, S. (Taylor & Francis, 2015)
Sulfonated polystyrene (SPS) and sulfonated polystyrene zeolite composite (SPS-Z) membranes were prepared by solution casting technique. SPS was synthesized using acetyl sulfate as a sulfonating agent in a reflux condenser under nitrogen atmosphere. The membrane casting was done without isolating the SPS. The SPS-Z membrane was fabricated by adding the zeolite to the SPS solution by the same technique. The synthesized SPS and SPS-Z membranes were characterized with Fourier transform infrared spectroscopy, thermogravimetric analysis, field emission scanning electron microscopy, and atomic force microscopy to identify the −SO3H functional group attached onto the polymer membrane, thermal stability, and surface morphology. The membranes were further examined for their water uptake capacity, swelling behavior, and degree of sulfonation. In addition, the performance of the fabricated membranes was examined based on their ion exchange capacity (IEC) and proton conductivity. The results revealed that both the membranes have good thermal and surface properties. The SPS-Z membrane has less swelling tendency than the SPS membrane due to lower water uptake capacity of SPS-Z membrane (2.5%) than the SPS membrane (3.5%). The proton conductivity of the SPS-Z membrane (1.11 × 10−5 S/cm) is higher than the SPS membrane (1.68 × 10−6 S/cm). The IEC capacity of SPS and SPS-Z membranes is found to be 0.03 and 0.17 meq/g, respectively. The proton conductivity of SPS and SPS-Z membranes is comparable with the Nafion 117® membrane (5.32 × 10−6 S/cm) under the same experimental conditions indicates that the fabricated membranes have the good potential for membrane applications, especially for fuel cell applications.